2022
DOI: 10.1021/acsanm.2c00693
|View full text |Cite
|
Sign up to set email alerts
|

Titania Nanomaterials for Sarin Decomposition: Understanding Fundamentals

Abstract: While TiO2-based materials have been attracting growing interest in combating chemical warfare agents (CWAs), their usefulness and details of chemical mechanisms remain unknown. In this study, we explored the potential of TiO2 nanomaterials as filter materials to degrade sarin (GB), one of the deadliest nerve agents. We performed joint experimental and theoretical studies of the breakdown of sarin gas on three different TiO2 nanomaterials: P25 TiO2, pure anatase TiO2 nanopowder, and mesoporous anatase TiO2. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…The crystallographic nature of all the synthesized and commercial samples was studied by the X-ray diffraction (XRD) method, with all the obtained patterns to be collected in Figure 1 a , while the calculated crystallite sizes, based on Scherer method [27] , to be presented in Table S1 . The P25 sample showed the presence of anatase and rutile phases which are found to be similar as reported previously [28] , [29] . The patterns of all the synthesized samples did not reveal well-defined reflections, a fact linked either to an amorphous nature or/and to very nanoscaled size of crystals.…”
Section: Resultssupporting
confidence: 88%
“…The crystallographic nature of all the synthesized and commercial samples was studied by the X-ray diffraction (XRD) method, with all the obtained patterns to be collected in Figure 1 a , while the calculated crystallite sizes, based on Scherer method [27] , to be presented in Table S1 . The P25 sample showed the presence of anatase and rutile phases which are found to be similar as reported previously [28] , [29] . The patterns of all the synthesized samples did not reveal well-defined reflections, a fact linked either to an amorphous nature or/and to very nanoscaled size of crystals.…”
Section: Resultssupporting
confidence: 88%
“…It was recently demonstrated that mesoporous metal oxides serve as powerful and reliable substrates to decompose lethal toxins (sarin, soman, etc.) (see, for example, refs and other work by this group). The large porosity (that is, the large surface area) ensures efficiency of the catalytic decomposition process; however, preparation of metal oxides in such architecture remains a challenge.…”
Section: Discussionmentioning
confidence: 86%
“…Metal oxides have been used in heterogeneous catalysis since the mid-1950s, and their robust nature, low cost, and ability to fully oxidize organic molecules make them a viable option for CWA filtration and decontamination . Several metal oxides that have been studied for sarin and CWA simulant decomposition include TiO 2 , Al 2 O 3 , Cu x O, , Fe 2 O 3 , , CeO 2 , , and ZrO 2 …”
Section: Introductionmentioning
confidence: 99%